Project Report on Secure Socket Layer Protocol - SANDEEP,SHITAL and SUMIT KUMAR (2007)
INTERNAL GUIDE: JAYAPRAKASH, MVJCE EXTERNAL GUIDE:KISHAN S VAIBHAVI,SC INFORMATION TECHNOLOGY,MIS POTENTIAL TECHNOLOGY
Keywords: Secure Socket Layer Protocol